2018
DOI: 10.1016/j.athoracsur.2017.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Extracardiac Fontan Takedown to an Intermediate Palliative Circulation

Abstract: Takedown to a superior cavopulmonary connection is an effective treatment option and, in some patients, acts as a bridge to subsequent redo Fontan completion or heart transplantation. An extended intermediate palliative circulation is tolerated for several years with reasonable oxygen saturation levels at rest. In our experience, an early takedown strategy to a superior cavopulmonary connection is the treatment of choice for acute Fontan failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Moreover, the performance of the Fontan system itself depends on several variables such as a good systolic and diastolic function, the sinus rhythm, low pulmonary pressure and vascular resistances, and good respiratory function. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is also debated if the Fontan outcome is influenced by pre-Fontan haemodynamic data. 6,[13][14][15][16][17][18][19][20] In fact, even if some studies underlined that the pre-Fontan haemodynamic data do not affect short-term post-Fontan outcome, [13][14][15] the majority of the authors agree on the importance of performing a pre-Fontan haemodynamic assessment to obtain the valuable data as the need for fenestration and anticipate the need for peri-operative systemic or pulmonary 18 Bridges et al underlined that the pulmonary artery size could not be considered alone as the major determinant of Fontan outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the performance of the Fontan system itself depends on several variables such as a good systolic and diastolic function, the sinus rhythm, low pulmonary pressure and vascular resistances, and good respiratory function. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is also debated if the Fontan outcome is influenced by pre-Fontan haemodynamic data. 6,[13][14][15][16][17][18][19][20] In fact, even if some studies underlined that the pre-Fontan haemodynamic data do not affect short-term post-Fontan outcome, [13][14][15] the majority of the authors agree on the importance of performing a pre-Fontan haemodynamic assessment to obtain the valuable data as the need for fenestration and anticipate the need for peri-operative systemic or pulmonary 18 Bridges et al underlined that the pulmonary artery size could not be considered alone as the major determinant of Fontan outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cutoffs are not universally established. [1][2][3][4][5][6][7][8][9][10][11] Therefore, a formula that can support the decision on fenestration could be useful. However, our results showed that the formula had a poor capability in identifying patients' need for fenestration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][51] Other strategies to address acute Fontan failure include listing for transplantation, 52 mechanical circulatory support, 53 or take down to a SCPC physiology. 54 A recent series identified 18 patients who underwent Fontan takedown to a SCPC; 2 during the Fontan procedure and 16 within the first 2 months. Seventeen patients survived the takedown.…”
Section: Failure To Progress To the Fontan Or Failure Of Fontan Pallimentioning
confidence: 99%
“…Of four patients surviving takedown, three (75%) underwent redo Fontan. Trezzi et al 3 in their series of 431 extracardiac Fontan (ECF) had 18 (4.2%) patients requiring takedown within two months, with 1 mortality. Redo Fontan candidacy probability was 35% for the 17 surviving takedown patients.…”
mentioning
confidence: 99%